2012
DOI: 10.1016/j.bpj.2011.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Role of Unsaturated Lipid and Ergosterol in Ethanol Tolerance of Model Yeast Biomembranes

Abstract: We present a combined atomic force microscopy and fluorescence microscopy study of the behavior of a ternary supported lipid bilayer system containing a saturated lipid (DPPC), an unsaturated lipid (DOPC), and ergosterol in the presence of high ethanol (20 vol %). We find that the fluorescent probe Texas Red DHPE preferentially partitions into the ethanol-induced interdigitated phase, which allows the use of fluorescence imaging to investigate the phase behavior of the system. Atomic force microscopy and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 71 publications
6
105
1
3
Order By: Relevance
“…2A; also see Fig. S2 in the supplemental material), probably because the membrane was damaged by this treatment, as emphasized in previous works (62)(63)(64)(65). We therefore tentatively estimated the thickness of the cell membrane by taking measurements of at least 5 different points per cell and made these measurements for 20 (each) untreated and ethanol-treated cells.…”
Section: Resultsmentioning
confidence: 88%
“…2A; also see Fig. S2 in the supplemental material), probably because the membrane was damaged by this treatment, as emphasized in previous works (62)(63)(64)(65). We therefore tentatively estimated the thickness of the cell membrane by taking measurements of at least 5 different points per cell and made these measurements for 20 (each) untreated and ethanol-treated cells.…”
Section: Resultsmentioning
confidence: 88%
“…Partial least-squares regression modeling of the correlation of the lipid composition data to fermentation kinetic data indicated that both ethanol production and maximum yeast cell density were highly correlated with yeast cell lipid composition. In particular, yeast strains that converted more sugar to ethanol had higher levels of specific phosphatidylcholine species that have previously been demonstrated to stabilize model membrane bilayers in a highethanol milieu (48). Strains that were unable to complete fermentation had higher concentrations of phosphatidylinositol during the early stages of fermentation (65).…”
Section: Lipid Composition In Yeast Alcoholic Fermentationsmentioning
confidence: 93%
“…This movement of ergosterol prohibits lipid interdigitation by compensating for the favorable Van der Waals forces that are diminished due to the increased head group spacing. Furthermore, the addition of the unsaturated lipid dioleoylphosphatidylcholine (DOPC) in synthetic bilayers demonstrated a similar protective effect to ergosterol (48). The lipid composition in yeast biomembranes is vastly more complex than the two-and three-component systems used in these studies.…”
Section: The Biophysical Effects Of Ethanol On Lipid Bilayersmentioning
confidence: 99%
“…In a model membrane of DPPC/DOPC/ergosterol, increasing the unsaturated lipid or sterol component co-operatively hinders the formation of the interdigitated phase [107]. DOPC is known to result in a more disordered and less tilted gel phase and can lead to phase separation at higher concentrations [108].…”
Section: Unsaturated Phospholipidsmentioning
confidence: 99%
“…DOPC is known to result in a more disordered and less tilted gel phase and can lead to phase separation at higher concentrations [108]. As a consequence, it was hypothesized that changes in the plasma membrane composition may play a role in the ethanol tolerance of yeast cells during fermentation ( [107] and references therein).…”
Section: Unsaturated Phospholipidsmentioning
confidence: 99%